El efecto del e-learning en la competencia comunicativa: producción oral en inglés (2020)
This research seeks to determine the effect of e-learning on oral English production (speaking), in terms of fluency, pronunciation and accent, vocabulary, accuracy grammar and details, of the undergraduate students of the Multidiomas Institute, a language learning center attached to the Universidad de la Costa. The approach of this research contemplates a quantitative design and a correlational scope with a quasi-experimental pre-test/post-test design, focused on the positivist paradigm. The sample selected was made up of a total of 21 beginner level students from the Multidiomas Institute, who developed their virtual language learning through 3 stages intervention during six progressive months. The analysis process is performed using a T- student statistic test. The main results conclude that the performance in the dimensions corresponding to pronunciation accent and accuracy were statistically and significantly lower before the intervention.